Meanings of nurses' role in Child and Adolescent Psychosocial Care Centers - Taliane Machado de Oliveira Leal; Caick Bispo de Souza; Isabela Martins Gabriel; Letícia Giácomo Alexandrin; Aline Cristiane Cavicchioli Okido; Lucía Silva; Diene Monique Carlos (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to analyze the meaning attributed to nurses' role in mental health care in Child and Adolescent Psychosocial Care Centers. Methods: qualitative research, anchored in the paradigm of complexity. Data collection was carried out through online semi-structured interviews with ten nurses from São Paulo, between March and September 2022, being analyzed thematically. Results: the diversity and specificity of a child and adolescent mental health clinic, with the need for expanded, territorial and intersectoral care, were unveiled in addition to a fragmented training in the area. There was a need for a deconstruction of being a nurse to make it possible to produce more inclusive and salutogenic practices. Final considerations: the need for training nurses with adequate knowledge and skills to care for the mental health of children, adolescents and their families is reinforced as well as permanent education of working teams.